A regulator of ubiquitin–proteasome activity, 2‐hexyldecanol, suppresses melanin synthesis and the appearance of facial hyperpigmented spots. (21st June 2013) - Hakozaki, T.; Laughlin, T.; Zhao, S.; Wang, J.; Deng, D.; Jewell‐Motz, E.; Elstun, L.
Summary: Background: 2‐Hexyldecanol has long been used in skin‐care products, but has not previously been reported as an active ingredient for skin benefits. Objectives: To evaluate 2‐hexyldecanol in in vitro and ex vivo systems and, if found to be active, progress it to topical clinical testing to determine effects on pigmentation in skin. Methods: 2‐Hexyldecanol was tested in melanocyte cell culture systems (B16 mouse melanoma cells and normal human melanocytes) for its effect on proteolytic activity and melanin production, in the absence and presence of the proteasome‐specific inhibitor, MG132. It was further tested in a human skin explant model for its effect on melanin production. Lastly, topically applied 2‐hexyldecanol was evaluated for its effect on the appearance of facial pigmentation in an 8‐week, randomized, double‐blind, vehicle‐controlled, split‐face incomplete block design study in Chinese women. Results: In submerged cell culture, 2‐hexyldecanol upregulated proteolytic activity and decreased melanin synthesis. These effects were antagonized by the proteasome‐specific inhibitor MG132. MG132, tested in the absence of 2‐hexyldecanol, increased melanin production. In a human skin explant model, topical 2‐hexyldecanol suppressed the production of melanin vs. a vehicle control. In a human clinical study in Chinese women ( n = 110 observations per test material), a 2‐hexyldecanol‐containing formulation significantly reduced the appearance of facial hyperpigmented spots vs. its control. Conclusions: These data indicate that regulation of proteasome activity is a viable target for control of melanin production, that 2‐hexyldecanol upregulates proteasomal activity in melanocytes, and that topical 2‐hexyldecanol reduces the appearance of hyperpigmentation.